High frequency of BRAF V600E mutations in ameloblastoma. Issue 5 (31st January 2014) - Kurppa, Kari J; Catón, Javier; Morgan, Peter R; Ristimäki, Ari; Ruhin, Blandine; Kellokoski, Jari; Elenius, Klaus; Heikinheimo, Kristiina
Abstract Ameloblastoma is a benign but locally infiltrative odontogenic neoplasm. Although ameloblastomas rarely metastasise, recurrences together with radical surgery often result in facial deformity and significant morbidity. Development of non‐invasive therapies has been precluded by a lack of understanding of the molecular background of ameloblastoma pathogenesis. When addressing the role of ERBB receptors as potential new targets for ameloblastoma, we discovered significant EGFR over‐expression in clinical samples using real‐time RT–PCR, but observed variable sensitivity of novel primary ameloblastoma cells to EGFR‐targeted drugs in vitro. In the quest for mutations downstream of EGFR that could explain this apparent discrepancy, Sanger sequencing revealed an oncogenic BRAF V600E mutation in the cell line resistant to EGFR inhibition. Further analysis of the clinical samples by Sanger sequencing and BRAF V600E‐specific immunohistochemistry demonstrated a high frequency of BRAF V600E mutations (15 of 24 samples, 63%). These data provide novel insight into the poorly understood molecular pathogenesis of ameloblastoma and offer a rationale to test drugs targeting EGFR or mutant BRAF as novel therapies for ameloblastoma. Published by John Wiley & Sons, Ltd. www.pathsoc.org.uk